Analysis of Gas Sweetening Unit for Natural Gas Using Membrane and aMDEA Technology with High CO2 Concentration > 60 % in XYZ Field - Zenda Christian Adhiatama; slamet slamet (Jurnal Rekayasa Kimia & Lingkungan)
The XYZ field in Jatibarang, West Java, processes 19 MMSCFD of gas with CO2 content over 60%, which does not meet the 8% CO2 limit required by the gas sales agreement. Traditional absorption technologies, while effective, have high energy demands. This study aims to optimize CO2 removal by combining membrane technology with aMDEA solvent-based absorption. Aspen Hysys software was used to simulate this combined approach, with aMDEA solvent chosen for its low corrosivity and high CO2 absorption rate. The membrane technology reduces CO2 levels initially, while the aMDEA solvent further lowers them to below 8%. Simulation results show that the combined system can reduce CO2 levels to 7.949% with a sweet gas flow rate of 7.108 MMSCFD. The process requires a membrane area of 4,611 m² and 172,960 lb/hr of solvent. This approach offers an effective solution for gas sweetening in fields with high CO2 concentrations, providing a more energy-efficient alternative to traditional methods.